PENGARUH PROGRAM PENDIDIKAN PROFESI GURU (PPG) TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN KALIDERES - Dea Wulan Ningrum; Ainur Rosyid (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The research carried out has the aim of knowing the effect of each teacher's educational program on teacher performance. The research carried out is research using quantitative methods by implementing it as a survey. There are several elementary schools that were sampled in this research, namely elementary schools in Kalideres sub-district with a total of 30 teachers. What is used to collect information is by implementing a questionnaire. The information obtained with the help of a questionnaire is used to obtain programs from both variables. The results obtained in this research can be seen that the calculated t value is 2.334 > 1.701 with a significance value of 0.027 < 0.05, so it can be interpreted that the teacher professional education program can have an influence on teacher performance.